Non-surgical Management of a Large Endodontic Lesion Using Diode Laser-Assisted Decompression and Photobiomodulation Therapy: A Case Report: Non-surgical laser management of endodontic lesion - Darmiani, Soheila; Saleh Jahromi, Soroush (Journal of Lasers in Medical Sciences, 2025)
Introduction: Endodontic periapical (PA) lesions are common sequelae of pulpal infections and often require root canal therapy (RCT) for resolution. Large lesions near vital anatomical structures are more important. A minimally invasive approach involving both diode laserassisted disinfection and photobiomodulation therapy (PBMT) might be more suitable as both are less invasive while suppressing deep infection and promoting tissue healing. Case Report: A 58-year-old female patient presented with a mandibular radicular cyst that extended from teeth #25 to #28 with a complicated buccal cortical perforation and proximity to the mental foramen. Treatment consisted of multi-visit root canal therapy with diode laser disinfection in the canals (980 nm, 200-µm fiber, 1 W, 1 second. for every 2 mm canal length, 4 passes) and PBMT (0.5 W, 30 seconds per point, 6 points; 7 sessions over 4 weeks) for the canals. Conclusion: This case demonstrates that a large PA lesion was resolved through a distinctive diode‑laser and PBMT, achieving significant healing in 10 months.